Experiential Marketing in an Age of Hyper-Connectivity Navigating the Customer Experience Journey. - Pomirleanu, Nadia; John-Mariadoss, Babu; Schibrowsky, John (Cambridge Scholars Publishing, 2022)
This book will serve as a first-stop, academic resource for every scholar of experiential marketing, aspiring marketing and consumer behavior student, agency executive, professor, and experiential marketing practitioner. It is as rigorous as it is informative and can be used as an introductory reading for experiential marketing courses and seminars, and as a playbook for future research development in the experiential marketing domain. This book will help readers learn the state of customer experience and experiential marketing, understand the use of experiential marketing in specific contexts.